Fixed Point Theorems Under Caristi’s Type Map on C∗ -Algebra Valued Fuzzy Soft Metric Space - Srinuvasa Rao, B; N.V.Kishore, G; Vara Prasad, Trkd (International Journal of Engineering and Technology, 2018)
In this paper, we present the extension of Caristi’s fixed point theorems for mappings defined on C∗-algebra-valued Fuzzy soft metric spaces. We establish the existence of simple proof of caristi’s type fixed point theorems in C∗-algebra-valued Fuzzy soft metric spaces and we give some examples which supports our main results.